Enhancing Nursing Education with Remote Access Laboratories - Bowtell, Leslie Alan; Moloney, Clinton; Kist, Alexander A; Parker, Victoria; Maxwell, Andrew; Reedy, Natasha (International Journal of Online and Biomedical Engineering (iJOE), 2012)
Abstractâ??Given the vast coverage area and dispersed population centres in which nursing professionals practice in Australia, Remote Access Laboratory (RAL) based learning activities would seem to be an ideal match. However while they are commonplace in engineering faculties; in other disciplines such activities are not widely used. This may well be due to the intricacies of these practicals not being as straightforward and readily reproducible as typical physics or science experiments. In our chosen case, the safe practice of intravenous pump driver operations and related clinical reasoning skills are important components for the training of both registered nurses and nursing students. The aim of this research project is to develop and trial remote access technologies that enable nursing students to test their knowledge, skills, and clinical reasoning with intravenous infusion pump drivers. This has been possible by extending the concept of RAL from a physical and tangible experiment, to more conceptual experimentation in any form conducted remotely. In such a context clinical reasoning becomes possible. This paper discusses a prototype system that has been built with collaborative input from the Faculty of Engineering and Surveying and the Department of Nursing and Midwifery. An initial evaluation with a group of nursing students has been completed to assess if such activities can assist with the training of student nurses. Previous work has identified the need to scaffold learning activities that rely on RAL technology; the key conclusion in this paper is that in the context of nursing this has to be taken a step further. RAL activities here require contextualisation to become an effective learning tool.